Global Diffusion of Protest : Riding the Protest Wave in the Neoliberal Crisis - Della Porta, Donatella, 1956- (Book collections on Project MUSE., 2017)
Recent years have seen a new development in the growth and spread of popular protest: protests that began as local, homogeneous events - such as Occupy Wall Street or the protests of the Arab Spring - quickly left their original locations, and local specificity, behind and became global. This book looks at the development of this wave of protests, with a specific eye on protests against austerity and neoliberal economic policies, and offers a global view, covering events in Turkey, Brazil, Venezuela, South Africa, Bosnia, Bulgaria, Ukraine, and other locations.